Science education in rural development - Hernandez, Dolores F. (Education quarterly.)
This paper focuses on the first part of a project which has as its major goal, uplifting the level of consciousness of science by improving the quality and content of science education in a pilot barangay. It ought to extend the outreach of science education by providing closer links between learning in school and the learning that takes place in the community. The project involved a large number of individuals from various agencies: the elementary school teachers of the chosen barangay, the local education officials, the barangay officials and the community (adult members who had children in school).